Las redes de la vivienda y el desarrollo sustentable en la centralidad de las ciudades de Oaxaca, México, 2000-2015 - Miguel-Velasco, Andrés Enrique; Martínez García, Karina Aidee; Pérez Pérez, Maribel; Moncada García, María del Rosario (El Colegio de México A.C., 2017)
Based on the concept of “adequate housing”, the analysis focuses on the housing influence in the sustainable development of the main cities of Oaxaca greater than 15 000 inhabitants, assuming that increased housing favors the development of our urban centers, by the creation of “central places”. Through a methodology of linear regression and network analysis, the results suggest that housing construction has increased during 2000-2015, but with a low contribution, because its impacts don't generate the centrality in the territory, for which reason it's required a review of the public policies.